Thriving Through Culture Shock: The Psychological and Adaptive Challenges of First-Year Nursing Students - Catanghal, Cheska Mae; Castillo, Franz Margaux; Catacutan, Ma. Kristine Joy; Catan, Fatima Haleya; Cejalvo, Geneva; Cruz, Joshua David Gabriel; Cruz, Mari Stefanie; Casimsiman, Denise Faye; Calacday, Charissa Rosamond (Journal of Interdisciplinary Perspectives, 2024)
First-year nursing students experience a demanding transition period, encountering culture shock due to academic rigor and unfamiliar expectations. Culture shock impacts an individual's psychological well-being and ability to adapt to the rigorous demands of nursing school. This study investigated the relationship between the level of culture shock and the adaptation and psychological well-being of first-year nursing students at a selected university in Quezon City. The study employed a descriptive correlational design to investigate the interplay between culture shock, student adaptation, and psychological well-being. A pre-screening form identified eligible individuals and was selected randomly using purposive sampling. A sample of 285 first-year nursing students consented and completed the questionnaire. All adapted instruments were presented on a 5-point Likert scale and were analyzed using Pearson’s correlation coefficient to examine the relationships between the variables. The study's findings showed a significant positive correlation with a statistical value of r = 0.592, p < 0.001, meaning that as culture shock increased, adaptation also increased. On the other hand, a significant positive correlation between culture shock and psychological well-being was found, with a statistical value of r = 0.520, p < 0.001, which suggests that as culture shock increases, psychological well-being increases as well. The study reported a moderate level of culture shock among first-year nursing students, emphasizing the importance of support programs, tailored methods, and accepting settings to aid adaptation and psychological well-being of the nursing students.